Analysis of Fatwa Characteristics of Sharia Economic Law - Syaukani Rahmat Rahmat; Koko Komarudin; Mohamad Anton Athoilllah (Yayasan Mentari Madani, 2023)
Sharia economic law fatwas are legal guidelines issued by scholars and fatwa bodies in the context of Islamic economics and business. This fatwa covers aspects of law, ethics, and economic principles that are Islamic principles. Analysis of the characteristics of Sharia economic law fatwa is important to understand the application of Islamic law in the economic and business context. In this analysis, we will look at the understanding and implementation of the characteristics of fatwas in business practice, the role and significance of fatwas in the Islamic economy, the influence of fatwas on investment decision-making, as well as the dynamics and evolution of fatwas in sharia economic law. The research method used is text analysis to understand the various opinions of experts regarding the meaning and role of the fatwa. Fatwas are considered important in Islam because they can solve problems that are not explicitly regulated in the Al-Quran and hadith. Fatwas have also developed since the time of the Prophet Muhammad until the modern era, involving companions, tabi'in, mujtahid imams, and contemporary scholars. This study aims to provide an understanding of the fatwa of Sharia economic law and its importance in Islamic economics. Through an analysis of the characteristics of fatwas and the research methods used, it is expected to provide a better understanding of the influence and implementation of fatwas in the context of sharia economics and business